How transdisciplinary integration, creativity and student motivation interact in three STEAM projects for gifted education?. (May 2023) - Lage-Gómez, Carlos; Ros, Germán
The study analyses the relationship between transdisciplinary integration, creativity and student motivation in three STEAM projects. It has been carried out over 3 years in a programme for gifted students. 152 students (11–12 years old), five teachers and four external professionals participated. The projects included a variety of scientific, humanistic and artistic activities, together with outings, the collaboration of experts and the creation of a transdisciplinary art-based final products. The research was carried out through the analysis of qualitative data (interviews, video-recordings, participant observation) using Atlas.ti8 within the framework of Activity Theory and statistical analysis of questionnaires. It shows how the transdisciplinary integration favoured a complex approach to knowledge with an essential role of the artistic-based transdisciplinary final products and fostered a plural approach to creativity. The active participation of the students favoured their motivation and involvement. The significant correlation between creativity, student motivation and transdisciplinary integration emerges as a key element in the STEAM projects implemented.